APLIKASI UNTUK MENDIAGNOSA PENYAKIT KISTA OVARIUM MENGGUNAKAN METODE FORWARD CHAINING - Dolly Indra (Jurnal Transformatika, 2014)
Expert System is designed to facilitate the public (patients) and the doctor or nurse in the decision to diagnose a cyst disease. And a patient can quickly and easily determine the type of illness suffered the cyst disease, as well as one of the alternatives in dealing with the type of disease and requires solutions to handle. The process of making these systems using Forward Chaining method for decision-making. Between system and user usesome questions in the form of a list of symptoms that have been there. The results of this system can facilitate in decision making doctor to diagnose the type of cyst disease suffered by the patient, causes, and treatment.